Comprehensive report of the BELARE 2022-2023 meteorite reconnaissance expedition in the Sør Rondane area, East Antarctica - Debaille, Vinciane; Schönbächler, Maria; Valdes, Maria; Maeda, Ryoga; Poudelet, Manu; Goderis, Steven; Heck, Philipp R.; Tollenaar, Veronica; Zekollari, Harry; Claeys, Philippe (情報・システム研究機構 国立極地研究所, 2023)
We provide a comprehensive overview of a reconnaissance expedition aimed at identifying new possible meteorite stranding zones in the surrounding of the Belgian Princess Elisabeth Antarctica (PEA) station in the Sør Rondane Mountains during the BELARE 2022-2023 field season. The team was composed of four scientists and one field guide. Several areas of interest were identified and daily searches occurred in two phases, first from a base camp and then from PEA. The first phase was in the Nils Larsenfjellet area, and a camp, accessible from the H.E. Hansenbreen (S72° 13.260' E22° 37.779'; altitude 1640 m), was set up from December 21 to 27, 2022. Systematic searches were performed in moraines and on blue ice areas (BIAs) during day trips, including the Verheyefjellet BIA, several BIAs surrounding an alignment of nunataks south of PEA, centered on S72° 18.403' E23° 13.191', and the Røysane nunatak at the eastern edge of Nils Larsenfjellet. Four meteorites were recovered during the first phase of the expedition, and another one in the second phase, also in the Nils Larsenfjellet area. In addition, nine surface ice samples and 18 kg of micrometeorite-bearing sediments were collected. Preliminary classification, performed on-site using magnetic susceptibility, tentatively indicated H and L chondrites. The recovered meteorites were transported in frozen state to the Royal Belgian Institute of Natural Sciences in Brussels to be thawed in vacuum conditions and classified based on their mineralogy. The Nils Larsenfjellet is identified as a potential new Dense Collection Area. departmental bulletin paper